Pengaruh Earning Per Share, Debt To Equity Ratio, Dan Current Ratio Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Food And Beverage Yang Terdaftar Di BEI Periode 2018-2020) - Ahmad Rifai; Ronny Malavia Mardani; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2021)
AbstrackThis study aims to determine and analyze the effect of earning per share, debt to equity ratio, and current ratio on firm value either partially. The method used in this research is multiple linier regression method. The research sample was 23 companies food and beverage taken by purposive sampling method. In this study using quantitative research. This type of research is explanatory research. The results of this study indicate that earning per share partially have a positive and significant effect on firm value, debt to equity ratio have a positive but not significant effect on firm value, current ratio have a negative and not significant effect on firm value. Keywords: Earning per Share, Debt to Equity Ratio, Current Ratio, Firm Value